New Onset vs Resolution of Central-Peripheral Rivalry–Type Diplopia in Patients Undergoing Epiretinal Membrane Peeling - Hatt, Sarah R. (JAMA Ophthalmol, 2018)
IMPORTANCE: The peeling of an epiretinal membrane (ERM) is commonly performed for poor visual acuity and/or metamorphopsia, but to our knowledge, its influence on central-peripheral rivalry (CPR)–type diplopia has not been rigorously studied. OBJECTIVE: To evaluate the occurrence of either resolution or new-onset CPR-type diplopia in patients undergoing ERM peeling. DESIGN, SETTING, AND PARTICIPANTS: This prospective cohort study was conducted from July 2014 to April 2018 at a tertiary referral medical center and included 33 adults with ERM who were undergoing peeling surgery with planned preoperative to postoperative analysis. INTERVENTIONS: A standardized diplopia questionnaire completed before undergoing and 6 months following ERM peeling. MAIN OUTCOMES AND MEASURES: For patients with CPR-type diplopia before ERM peeling (rated “sometimes” or more for distance straight ahead or reading using the diplopia questionnaire), we calculated the proportion with resolution of diplopia postpeel (“never” for distance straight ahead and reading on the diplopia questionnaire) and compared clinical characteristics between those with resolution and those without. For patients with no diplopia prepeeling (“never” for distance straight ahead and reading on the diplopia questionnaire), we calculated the proportion with new-onset CPR-type diplopia postoperatively and compared clinical characteristics between those with new-onset diplopia and those who remained without diplopia. RESULTS: Of 33 patients (median age, 67 years [range, 51-87 years]; 18 men [55%]), 12 (36%) had CPR-type diplopia preoperatively and 21 (64%) did not have diplopia preoperatively. Six months postoperatively, 4 of 12 patients with diplopia (33%; 95% CI, 10%-65%) had resolution of diplopia, and 4 of 21 patients without diplopia (19%; 95% CI, 5%-42%) had new-onset diplopia. Better postoperative operated-eye visual acuity appeared somewhat associated with new-onset diplopia postoperatively (mean [SD] visual acuity, 0.08 [0.10] logMAR; approximately 20/25 vs 0.34 [0.33] logMAR; approximately 20/40; difference, −0.27; 95% CI, −0.62 to 0.09; P = .07), as did greater postoperative aniseikonia (14% [5%] vs 6% [4%]; difference, 8%; 95% CI, 2%-13%; P = .04). CONCLUSIONS AND RELEVANCE: These data suggest that epiretinal membrane peeling may result in resolution of diplopia in some patients but new-onset diplopia in others. These findings may be valuable when counseling patients regarding the risks of new-onset diplopia.